2010
DOI: 10.1586/eog.10.7
|View full text |Cite
|
Sign up to set email alerts
|

Hypothermia for hypoxic–ischemic encephalopathy

Abstract: Moderate to severe hypoxic-ischemic injury in newborn infants, manifested as encephalopathy immediately or within hours after birth, is associated with a high risk of either death or a lifetime with disability. In recent multicenter clinical trials, hypothermia initiated within the first 6 postnatal hours has emerged as a therapy that reduces the risk of death or impairment among infants with hypoxic-ischemic encephalopathy. Prior to hypothermia, no therapies directly targeting neonatal encephalopathy secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 98 publications
(93 reference statements)
2
76
0
3
Order By: Relevance
“…52 Four pivotal multicenter clinical trials of hypothermia for neonates with moderate-to-severe HIE (CoolCap, NICHD Neonatal Research Network, Total Body Hypothermia and Infant Cooling Evaluation) have led to widening adoption of cooling as a treatment of choice for term and near-term neonates with HIE. 9 Four published meta-analyses, including a Cochrane review, demonstrated a consistent beneficial effect for moderate hypothermia with reduction of risk of the combined outcome, death or neurodevelopmental impairment at B2 years ( Figure 3). All meta-analyses of several main trials and well-described phase I and II randomized studies, which included outcome information, demonstrate consistent relative risk of death or disability of B0.75 and a 95% confidence interval between 0.60 and 0.90.…”
Section: Limited Endogenous Neurogenesis Following Hypoxic Ischemic Imentioning
confidence: 95%
See 1 more Smart Citation
“…52 Four pivotal multicenter clinical trials of hypothermia for neonates with moderate-to-severe HIE (CoolCap, NICHD Neonatal Research Network, Total Body Hypothermia and Infant Cooling Evaluation) have led to widening adoption of cooling as a treatment of choice for term and near-term neonates with HIE. 9 Four published meta-analyses, including a Cochrane review, demonstrated a consistent beneficial effect for moderate hypothermia with reduction of risk of the combined outcome, death or neurodevelopmental impairment at B2 years ( Figure 3). All meta-analyses of several main trials and well-described phase I and II randomized studies, which included outcome information, demonstrate consistent relative risk of death or disability of B0.75 and a 95% confidence interval between 0.60 and 0.90.…”
Section: Limited Endogenous Neurogenesis Following Hypoxic Ischemic Imentioning
confidence: 95%
“…7,8 However, in the clinical trials demonstrating benefit, a significant number of the HIE infants still died or survived with neurologic and functional impairment. 9 Stem cell regenerative therapies offer great promise in a variety of degenerative diseases including neurological disorders. Stem cells from different sources, such as neural stem/progenitor cells derived from either fetal tissue or embryonic stem-induced pluripotent stem cells, MSCs, human umbilical cord blood (HUCB)-derived stem cells or HUCB mononuclear cells, have been utilized in several animal models of neurological diseases.…”
Section: Introductionmentioning
confidence: 99%
“…During the last 2 decades, evidence from experimental and clinical studies proved that therapeutic hypothermia reduces cerebral injury and improves neurological outcome provided that cases of HIE are early diagnosed [15][16][17] . Many studies of perinatal asphyxia have measured several biologic markers (brain-specific creatine kinase, neurone specific enolase, S 100 B protein, Activin-A, hypoxanthine, erythropoietin, and lactate dehydrogenase in serum or cerebrospinal fluid), but the tests are usually performed late after birth, when the infants may already have HIE [18][19][20][21] .…”
Section: Discussionmentioning
confidence: 99%
“…Фазы энергетической недостаточности Клинические и экспериментальные исследования пока-зывают, что ГИП развиваются через две фазы -первич-ную и вторичную энергетическую недостаточность [3][4][5][6].…”
Section: патофизиологические механизмы гипоксически-ишемических поражunclassified
“…Высокая степень первичной энер гетической недостаточности способствует дальней-шему повреждению [3][4][5][6]. Между первичной и вторичной фазой энергетической недостаточности есть короткий, так называемый латентный, период восстановления кровото-ка, который характеризуется нормальным церебральным метаболизмом.…”
Section: патофизиологические механизмы гипоксически-ишемических поражunclassified